Hubungan Pengetahuan Gizi dan Siklus Menstruasi dengan Kejadian Anemia pada Remaja Putri Aliyah Pondok Karya Pembangunan Al-Hidayah Provinsi Jambi - hayati, indah puji; Fatmawati, Tina Yuli; Jeki, Andicha Gustra (Universitas Baiturrahim, 2025)
Anemia is a health condition in which the number of red blood cells or hemoglobin is less than normal (<12 g/dl). Factors that can cause anemia are nutritional knowledge and abnormal menstrual cycles. The purpose of this study was to determine the relationship between nutritional knowledge and menstrual cycles with the incidence of anemia in female adolescents at Aliyah Islamic Boarding School in Jambi Province. This type of research is a quantitative study with a cross-sectional design conducted at Al-Hidayah Islamic Boarding School in Jambi. The time of this research was conducted in February-June 2024. Based on the population of female adolescents, namely 234 female adolescents, the sample was taken using the Slovin formula, namely 77 respondents with the sampling technique used, namely proportional random sampling. Data collection by interviewing, filling out a nutritional knowledge questionnaire and checking Hb. The data analysis used was univariate and bivariate analysis using the Spearman correlation test. The results of the study showed that the percentage of Nutrition Knowledge was lacking as many as 45 female students (58.4%), Menstrual Cycle was abnormal as many as 47 respondents (61%), the incidence of anemia of respondents experienced anemia as many as 39 respondents (50.6%). There is a significant relationship between Nutrition Knowledge and the incidence of anemia, the significance value (p-value) is 0.001 (<0.05). There is a significant relationship between the menstrual cycle and the incidence of anemia, the significance value (p-value) is 0.000 (<0.05). It can be concluded that nutritional knowledge and menstrual cycles are related to the incidence of anemia in adolescent girls.